China is actively implementing health impact assessment legislation - Wang, Quansheng; Zhang, Xiaoyi; Zhang, Qi (Frontiers in Public Health, 2025)
The health impact assessment system is imperative for prioritizing prevention and establishing “people’s health” as a central tenet. Implementing this system is contingent on the existence of “perfect legislation.” Although China has already begun to implement health impact assessment legislation, it is still in the exploratory stage and faces numerous internal and external legislative challenges. The civil and criminal legal norms supporting the health impact assessment must be established and perfected within the framework of developing the fundamental law. Supportive measures are being implemented, such as training skilled professionals, prioritizing underdeveloped regions, and using government evaluations and incentives, to promote the integration of health impact assessment into Chinese legislation. These efforts are directed at improving China’s legal system and health impact assessment coordination mechanisms, with the overarching objective of improving public welfare. This trend is in response to the growing social expectations of a better quality of life.